If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6m-7-4-16=-23
We simplify the equation to the form, which is simple to understand
6m-7-4-16=-23
We move all terms containing m to the left and all other terms to the right.
+6m=-23+7+4+16
We simplify left and right side of the equation.
+6m=+4
We divide both sides of the equation by 6 to get m.
m=0.666666666667
| 5x+10+7x=22 | | 2k+1=15 | | 2(c)+2(c)+16=72 | | 8q+17=4(3+2q) | | 3z^2-300=0 | | 3x+y=464 | | (2+x)+(5+(2+x))=180 | | 4x+16=2x+18 | | 9+5x-3x=13 | | (2+x)+(5+2+x)=180 | | 2x+5=5x+11 | | -x=29 | | 16(-20+x)=-592 | | 0.142857(14-7q)-2=-2(0.5q+3)+6 | | 2(y-5)=-24 | | -4(3-x)+6=2x-6 | | 2m=17 | | 3(6d-7)=15d+3 | | 53=6x-x+8 | | 2x^2+19x=174 | | a-8.06+7.02=18.4 | | x+x=650 | | 52=x+95 | | w+12.2=-7.2 | | s=6+-3 | | -3+4x+7x=129 | | x+y=650 | | 3x+1+6=33 | | 2x^2-3x=-2x+3 | | 16(x-1)+22x=231 | | 88=-8x | | 18=4x+1.5y |